Identification of Floating Marine Debris in The Banda Aceh Estuary - Koko Ondara; Ruzana Dhiauddin (Politeknik Kelautan dan Perikanan Dumai, 2021)
The coastal area of Banda Aceh City have the potential to be polluted by waste from the mainland as much as 45.41 tons/day. One source of land waste is the Krueng Aceh river, the river has dense residential areas and high community activities such as ports, ship repairs, traditional markets, recreation and fishing activities. This study aims to identify floating debris in the Krueng Aceh estuary. Data collection was carried out at the mouth of the river using a debris trap mounted on the ship that moves periodically and the research time was based on tidal charts. The results showed that type of marine debris found is plastic, cloth, processed wood, rubber and metal. Plastic debris is the most common debris found by 89 % on the surface of the Krueng Aceh estuary at spring tide and neap tide. The highest amount of debris is found in the morning 09.50 AM and 03.32 PM in the evening.